Product Quality towards Product Purchase Decisions - Lunanda, Ivana Destine (Adpebi Science Series, 2022)
The purpose of this study was to prove the effect of product quality on product purchase decisions at PT Bank Mestika Dharma, Tbk Capem Sumatra Medan. The subject of this research is the customer of PT Bank Mestika Dharma, Tbk Capem Sumatra Medan. The population in this study was 238 customers and the sample was 70 people from the population with the sample calculation using the slovin formula. The data collection technique used a questionnaire in which the research method used was a quantitative method. Based on the t-test, it was found that the value of 0.075 means that the better the product quality, the greater the level of purchasing decisions. With a significance value of 0.041, it means that this variable has a significant effect on purchasing decisions, where the significance value is <0.05. Based on the results of the regression calculation, it can be seen that the coefficient of determination (R2) obtained is 0.256. This means that 25.6% of the variation in the Purchasing Decision variable can be explained by the Product Quality variable, while the remaining 74.4% is explained by other variables not proposed in this study.